Improved real and reactive power transmission usage allocation methods for deregulated power systems [electronic resource] - Saifulnizam Abd. Khalid, 1975-; Mohd. Wazir Mustafa; Fakulti Kejuruteraan Elektrik (2009)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2009